PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY LEARNING BERBASIS LESSON STUDY FOR LEARNING COMMUNITY PADA MATERI SISTEM KOLOID TERHADAP HASIL BELAJAR SISWA SMAS ADABIAH PADANG - Lala Denada; Andromeda Andromeda (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
Learning that is still centered on the teacher makes students not actively involved in the learning process. Therefore, an efficient learning model is needed to help students develop higher order thinking skills by actively involving students. The selection of learning models that support students actively in the learning process is one of the factors that determine student learning outcomes. One of the learning models that involve students actively is guided inquiry learning.. To support the implementation of the guided inquiry learning model optimally, it is necessary to have a process of planning and reflecting on learning, namely lesson study for learning community (LSLC). This study aims to analyze the effect of applying the LSLC-based guided inquiry learning model on colloidal system material on student learning outcomes at Adabiah Padang High School. This type of pseudo-experimental research uses a pretest-posttest control group design. The data obtained were normal and homogeneous. From the t-test results obtained tcount (2.579) > ttable (1.997). So it can be concluded that the learning outcomes of students who use the LSLC-based guided inquiry learning model are significantly higher than the learning outcomes of students without using the LSLC-based guided inquiry learning model on colloidal system material at Adabiah Padang High School.